A Simple and Reproducible In Vivo Rabbit Phonation Model for Glottic Insufficiency. (26th January 2023) - Swift, William M.; Churnin, Ian T.; Hamdi, Osama A.; Strumpf, Andrew M.; Koehn, Heather A.; Cottler, Patrick S.; Daniero, James J.
Abstract: Objective: The objective of this study is to describe an in vivo rabbit phonation model for glottic insufficiency that is simple and reproducible by means of unilateral transcricothyroid laryngeal muscle stimulation and high‐speed video recordings of evoked phonation. Study Design: Nonrandomized controlled animal trial. Setting: Academic medical center. Methods: A single operation including evoked phonation with bilateral and unilateral transcricothyroid laryngeal muscle stimulation conditions was modeled using 6 New Zealand white rabbits. The effect of stimulation method on glottic cycle, pitch, and loudness was compared. Endoscopic recordings using 5000 frames‐per‐second image capture technology and audiologic recordings were obtained for all phonation conditions. Primary outcome measures included means of maximum glottal area (MGA)/length pixel ratio, right and left amplitude/length pixel ratios, calculated cycle frequency, auditory recorded frequency, and maximum auditory intensity. Measurements were obtained via pixel counts using ImageJ. Results: Mean MGA/length was significantly greater with unilateral, 20.30, vs bilateral, 9.62, stimulation ( P = .043). Mean frequency of 479.92 Hz vs 683.46 Hz ( P = .027) and mean maximum intensity of 76.3 dB vs 83.5 dB ( P = .013) were significantly increased from unilateral to bilateral stimulation. There was no significant difference in mean right amplitude/length between unilateral and bilateral. Conclusion: The described model demonstrates a simple and reproducible means of producing glottic insufficiency due to unilateral vocal fold bowing and represents a pathway for better understanding the biomechanics and pathophysiology of glottic insufficiency due to superior laryngeal nerve injury and vocal fold immobility and offers the potential to compare treatment modalities through in vivo study.